How Will the Use of Technology in Translation and Testing Affect Language Learning? - David Michael Bourne (Bina Nusantara University, 2014)
Technology has an ever increasing impact on how we work and live. Article adressed the issue of the impact of technology in two key areas of language learning. On the one side learners increasingly used technology to translate. Given this trend, was there any real need to learn a language. On the other side, educational institutions increasingly used technology to rate language proficiency. Given this trend, would the work of the teacher become less and less important. The survey was conducted by using quantitative method. The respondents’ age range was 18-25. There were 53 respondents, 35% were male and 65% were female. The instrument was a questionaire having 9 questions describing the students’ reliance on computer in translation. It can be concluded that learners of English indicate that they accept and welcome the role of technology in language learning, but there is a doubt that the role and participation of humans in the learning process will be completely replaced. The human element remains an important ingredient. (EE)